Performance improvement of a micro-structured gas separator utilizing the Soret effect - Takeshi KYODA; Takumi SAIKI; Sohei MATSUMOTO; Shinya WATANABE; Naoki ONO (Journal of Thermal Science and Technology, 2022)
The Soret effect is a phenomenon in which the components of mixed fluids are separated by a temperature gradient. This study investigated a simple and low-cost technique for extracting high concentration hydrogen (H2) by utilizing the Soret effect in a H2-carbon dioxide mixed gas. Previous research by the authors attempted to improve the efficiency of H2 separation by applying a temperature difference to a network of separators with a continuous structure (the Burgers cascade) and enabling a mixed gas throughflow. One of the problems in that study was the impairment in separation performance that occurred due to the remixing of the components separated by flows within the device cells. Therefore, to resolve this problem, the present study conducted numerical simulations for gas flow, temperature distribution, and H2 concentration and studied the effect of inserting an additional structure (a partition) to prevent gas remixing at first. Based on the simulation results, experiments were conducted using the Burgers cascade in a device with partitioned cells. The results confirmed that the partitions improved the separation of H2 by up to about 1.6 times compared with conventional devices.